2021
DOI: 10.34123/semnasoffstat.v2020i1.398
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Udara Dan Potensi Transmisi Covid-19 Di Pulau Jawa

Abstract: Penularan SARS-CoV-2 di Indonesia semakin mengkhawatirkan. Pandemik COVID-19 tidak hanya berdampak pada individu yang terinfeksi langsung, tetapi juga berimbas kepada para penyintas kolateral, yaitu mereka yang kehidupannya ikut terdisrupsi akibat krisis. Pulau Jawa adalah episentrum penularan COVID-19 di Indonesia. Beberapa studi menunjukkan bahwa kejadian COVID-19 memiliki hubungan yang erat dengan tingginya konsentrasi zat partikulat di udara. Penelitian ini bertujuan untuk mengetahui hubungan antara kualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Spatial statistics have mainly been used to analyze the socioeconomic and demographic risk factors of COVID‐19 (Iyanda et al., 2020 ; Sannigrahi, Pilla, Basu, Basu, & Molter, 2020 ; Sun, Matthews, Yang, & Hu, 2020 ; Urban & Nakada, 2021 ). Air quality (Maiti et al., 2020 ; Zulkarnain & Ramadani, 2020 ), health infrastructure (Mollalo, Vahedi, & Rivera, 2020 ), and mobility (Nian et al., 2020 ) have also been examined and linked to COVID‐19 risk and transmission. We have seen an influx of both spatial and spatiotemporal statistical methods applied to COVID‐19, with many studies utilizing the results to produce risk and social vulnerability maps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial statistics have mainly been used to analyze the socioeconomic and demographic risk factors of COVID‐19 (Iyanda et al., 2020 ; Sannigrahi, Pilla, Basu, Basu, & Molter, 2020 ; Sun, Matthews, Yang, & Hu, 2020 ; Urban & Nakada, 2021 ). Air quality (Maiti et al., 2020 ; Zulkarnain & Ramadani, 2020 ), health infrastructure (Mollalo, Vahedi, & Rivera, 2020 ), and mobility (Nian et al., 2020 ) have also been examined and linked to COVID‐19 risk and transmission. We have seen an influx of both spatial and spatiotemporal statistical methods applied to COVID‐19, with many studies utilizing the results to produce risk and social vulnerability maps.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a spatial lag model (SLM) can be used to examine how events at a location influence similar events in surrounding locations (i.e., spatial interaction); and a spatial error model (SEM) can be applied to account for autocorrelation of the residuals (Iyanda et al., 2020 ; Maiti et al., 2020 ; Mollalo, Vahedi, et al, 2020 ; Nian et al., 2020 ; Sannigrahi et al., 2020 ; Sun, Di, Sprigg, Tong, & Casal, 2020 ; Urban & Nakada, 2021 ); see Table 1 . For COVID‐19, spatially combined autoregressive models (SAC) have also been used as a combination of the previous models to simultaneously consider spatial lag and spatial error parameters (Sun, Di, et al., 2020 ; Zulkarnain & Ramadani, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, SLM can be used to scrutinize how actions at a location influence similar actions in nearby locations (i.e., spatial interaction); and SEM can be useful to account for autocorrelation of the residuals ( [49]; [46]; [2]; [21];[40]; [42]; [41]. From Table 1, it can be observed that spatially combined autoregressive models (SAC) have also been used as a mixture of the previous models to concurrently consider SEM and SLM in the study COVID-19 [58]; [69]. [18], [19], [21] and [23] uses SAC to analyze the characteristics of COVID-19 at various spatial levels of aggregation.…”
Section: Global Regression Modellingmentioning
confidence: 99%
“…Travaglio dkk. (2021) serta Zulkarnain & Ramadani (2021) menemukan asosiasi positif antara polusi udara dan transmisi COVID-19. Paparan jangka panjang terhadap polusi udara berhubungan dengan risiko beberapa penyakit pernapasan, dimana individu dengan prakondisi kesehatan tersebut akan lebih rentan terhadap infeksi COVID-19 (Zheng dkk., 2021).…”
Section: Kerentanan Pandemiunclassified